Plastic pollution and health metrics in wild juvenile green sea turtles (Chelonia mydas) from two Ecuadorian national parks: Galápagos and Machalilla - Muñoz-Pérez, Juan Pablo; Lewbart, Gregory A.; Toapanta, Tania; Chadwick, Helen; Okoffo, Elvis D.; Alarcón-Ruales, Daniela; Zurita-Arthos, Leo; Jones, Jen S.; Cisneros, Fernando; Moreira-Mendieta, Andres; Vintimilla-Palacios, Cristina; Miranda, Cristina; et al. (Frontiers in Amphibian and Reptile Science, 2024)
Marine vertebrates, particularly green sea turtles, are highly susceptible to plastic pollution via ingestion or entanglement. In this study, 46 juvenile green sea turtles (Chelonia mydas) in two Ecuador national parks (Galápagos and Machallilla) were investigated to assess the prevalence of plastic in their feces and were compared with a suite of health metrics. Fourier transform infrared spectroscopy (FT-IR) revealed that sea turtles had x̄=4.4±5.2 (range:0-19) microplastics (MPs)/g in feces. Furthermore, these levels differed according to the sampling location, with the most polluted samples found in the Galápagos Marine Reserve (GMR). Fibers were the most common type, x̄=3.8±4.5 (range:0-16) MPs/g, and polyvinyl alcohol (PVOH), x̄=1.4±2.2 (range:0-10) MPs/g, and polyacrylates (PMMA) x̄= 0.95±1.3 (range:0-5) MPs/g were the most common synthetic polymers identified by FT-IR. Based on the MPs/g in feces, we estimated that the daily ingestion of MPs by the sampled green sea turtle populations varied from a mean of 312±409 (range:0-1898) MPs/day to a mean of 430±563 (range: 0-2610) MPs/day. Simultaneously, we tested a complementary methodology for quantifying synthetic mass polymer concentrations within the same fecal matter, pressurized liquid extraction with doubleshot pyrolysis-mass spectrometry gas chromatography (Pyr-GC/MS). This method detected polyethylene (PE) x̄=367±1158 (range:0-6096) µg/g as the highest mass polymer concentration in feces, and polypropylene (PP) x̄= 155±434 (range:0-2944) µg/g was also abundant. The analysis also showed that the levels of plastics detected varied by location, with the most polluted samples located in the GMR but not in the same areas identified by FT-IR. Of the sea turtles in our sample population, 98% had detectable levels of plastic pollution in their feces, as identified by both FT-IR and Pyr-GC/MS techniques. Although both methods are reliable, they yielded slightly different results owing to methodological variations. However, both techniques agreed that animals in the GMR were more polluted. Despite being clinically normal, further research is needed to understand the potential health implications, given that lower concentrations of lymphocytes, total proteins, and ionized calcium were detected in addition to higher levels of heterophils and monocytes in sea turtles, which exhibited a higher prevalence of plastic contamination in both their feces and environment.